The Use of Modern Technologies as A Factor in Improving the Teaching Quality - Abdukhalikova Marhabo; Berdiqobilovna (Genius Publishing Group, 2022)
The article deals with the problems of using interactive methods, as well as the introduction of technology for the development of critical thinking in the classroom.
Keywords: Information technology; development; thinking; professional competence